2018
DOI: 10.1017/pao.2018.10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Bartonella species and haemoplasmas in wild African buffalo (Syncerus caffer) in Mozambique, Africa

Abstract: The African buffalo (Syncerus caffer), a mammal species whose population is declining, can play a role as a reservoir or carrier of a wide number of arthropod-borne pathogens. Translocation procedures have been used as an alternative approach for species conservation. However, the veterinary aspects of this sort of procedures are extremely important to minimize the impact on animal health. In order to detectBartonellaand haemoplasmas, two important group of bacterial that have an impact in both human and anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
0
15
0
2
Order By: Relevance
“…The only study in a bovine included 97 wild buffaloes (Syncerus caffer) from Mozambique using species-specific primers, which detected both M. wenyonii and Ca. M. haematobovis, including four cases of coinfection (Gonçalves et al, 2018). Among suids, only wild boars (Sus scrofa) have been investigated.…”
Section: Accepted Articlementioning
confidence: 99%
“…The only study in a bovine included 97 wild buffaloes (Syncerus caffer) from Mozambique using species-specific primers, which detected both M. wenyonii and Ca. M. haematobovis, including four cases of coinfection (Gonçalves et al, 2018). Among suids, only wild boars (Sus scrofa) have been investigated.…”
Section: Accepted Articlementioning
confidence: 99%
“…At present, there are 5 kinds of Bartonella related to ruminants: B. bovis, B. chomelii, B. schoenbuchensis, B. capreoli, and B. melophagi. An increasing number of Candidatus Bartonella species and different genotypes have been reported in ruminants (4)(5)(6)(7). Previous studies have shown that Bartonella DNA is amplified in ruminant-related blood-eating arthropods, including Hippoboscidae flies from Europe and Algeria (8,9), Stomoxys spp.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, five Bartonella species named Bartonella bovis , Bartonella chomelii , Bartonella schoenbuchensis , Bartonella capreoli and Bartonella melophagi have been associated with ruminants. In addition, an expanding number of Candidatus to Bartonella species and different genotypes have been globally reported in ruminants (Dahmani et al, 2017; Gonçalves et al, 2018; Raya et al, 2018; Razanske et al, 2018). Interestingly, these species and recently detected genotypes are phylogenetically related and exclusively associated with these animals (Kosoy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although Bartonella infections have been reported in cattle worldwide (Antequera‐Gómez et al, 2015; Bai et al, 2013; Bermond et al, 2002; Gutiérrez et al, 2014; Roilan, Rousset, Scola, Duquesnel, & Raoult, 2003; Tsai et al, 2011), only two studies reported Bartonella in buffaloes so far (Bai et al, 2013; Gonçalves et al, 2018). While the first study isolated B. bovis in Asian buffaloes ( Bubalus bubalis ) from Thailand, the second amplified Bartonella DNA in wild African buffaloes ( Syncerus caffer ) from Mozambique.…”
Section: Introductionmentioning
confidence: 99%